2020
DOI: 10.3389/fmed.2020.00165
|View full text |Cite
|
Sign up to set email alerts
|

Antinuclear Antibodies With a Homogeneous and Speckled Immunofluorescence Pattern Are Associated With Lack of Cancer While Those With a Nucleolar Pattern With the Presence of Cancer

Abstract: Background: Different antinuclear antibody (ANA) patterns have been associated with the presence of cancer, while other are typically seen in autoimmune diseases. This study aims to investigate the association between ANA and cancer, focusing on patients with ANA with a nucleolar indirect immunofluorescence (IIF) pattern. Materials and Methods: ANA patterns and positivity of antibodies against nuclear antigens (NA), in particular those responsible for a nucleolar ANA pattern and/or associated with systemic scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Finally, Gauderon et al recently conducted a retrospective study of cancer risk in patients with autoantibodies detected by immunofluorescence [35]. In addition to an increased incidence of cancer in patients with anti-RPC1, their findings also support the concept of high-and low-risk subtypes within autoimmune diseases.…”
Section: Acas and Relationships With Cancermentioning
confidence: 89%
See 2 more Smart Citations
“…Finally, Gauderon et al recently conducted a retrospective study of cancer risk in patients with autoantibodies detected by immunofluorescence [35]. In addition to an increased incidence of cancer in patients with anti-RPC1, their findings also support the concept of high-and low-risk subtypes within autoimmune diseases.…”
Section: Acas and Relationships With Cancermentioning
confidence: 89%
“…In addition to an increased incidence of cancer in patients with anti-RPC1, their findings also support the concept of high-and low-risk subtypes within autoimmune diseases. Interestingly, the ACA pattern had the lowest relative cancer risk of any pattern, although the study was underpowered to reach statistical significance [35].…”
Section: Acas and Relationships With Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, the significance of the ANA patterns is ignored in clinical practice and research. A recent study showed that the presence of ANAs with a nucleolar pattern was associated with an increased relative risk of cancer (15). Furthermore, the significance of ANA patterns, especially the cell-cycle related ANAs, was emphasized in carcinoma (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different ANA patterns have been associated with the presence of cancer. ANAs with a homogeneous and speckled immunofluorescence pattern are associated with lack of cancer, while those with a nucleolar pattern are associated with the presence of cancer (15). The positivity for the anti-centromere antibody is reported as a statistically significant risk factor for cancer (16).…”
Section: Introductionmentioning
confidence: 99%